Introducing LexEst: a quick and efficient vocabulary test for assessing vocabulary knowledge in L2 Estonian - Lõo, Kaidi; Leppik, Katrin; Malmi, Anton; Bleive, Agu; Bertram, Raymond (Cambridge University Press (CUP), 2026)
This study presents the creation and validation of LexEst, a short 5-minute test to assess vocabulary knowledge in Estonian. Our freely accessible test consists of 90 items and is designed for L2 speakers of Estonian. LexEst is modeled after the original Lexical Test for Advanced Learners of English. Similarly to other test variants, our test has been adapted to assess vocabulary knowledge at varying proficiency levels. Our findings demonstrate that LexEst provides an objective measure of the Estonian vocabulary of L2 learners, aligning well with subjective language proficiency indicators, such as self-assessed skills. In addition, higher LexEst scores and shorter response times are associated with higher CEFR-level language courses and a greater daily use of Estonian. Higher LexEst scores are also associated with an earlier age of acquisition in Estonian and a higher perceived importance of learning Estonian.